Partial motor status epilepticus - Gilberto Rebello de Mattos; José C. Rollemberg Filho (Arquivos de Neuro-Psiquiatria)
We report the case of a young female patient with photosensitive primary epilepsy who presented partial motor status epilepticus provoked by the act of shutting the eyes. Clinical, EEG and neuroimage data are presented and discussed.